Retrospective analysis of HDFN due to ABO incompatibility in a single institution over 6 years. Issue 3 (25th January 2018) - Matteocci, A.; De Rosa, A.; Buffone, E.; Pierelli, L.
SUMMARY: Objectives: To study the rate of ABO haemolytic anaemia of fetus and newborn (HDFN) in one institution over 6 years. Background: ABO major incompatibility between mothers and their newborns occurs in about 10% of births. So, mothers with an O blood group may form IgG‐class antibodies against A and B antigens, which could pass across the placenta and lead to a variable degree of HDFN in the newborn. Methods: At our institution, we have reviewed data regarding ABO‐based HDFN in the last 6 years. Results: We found that, in 28 089 deliveries, an ABO major incompatibility between mothers and newborns occurs in 11% of cases, with 72% of O/A and 28% of O/B incompatibility. In turn, 23% of these newborns had an eluate‐confirmed positive direct antiglobulin test [DAT; 74% (511) were due to anti‐A and 26% (179) to anti‐B], with 1·0% requiring invasive treatments (exchange transfusion or intravenous immunoglobulin). Overall, 2·5% of the total newborns had a positive DAT for an anti‐A or anti‐B antibody, and 0·11% required invasive treatment in addition to phototherapy for their HDFN. Conclusions: Serological ABO HDFN is a relatively frequent event when an O‐A/O‐B incompatibility between mothers and their newborn occurs and, in most cases, translates into a self‐limiting disease, with a small number of newborns requiring invasive treatments. The DAT test, although not predictive of disease severity, appears to be a useful tool to monitor babies born from O‐A/O‐B‐incompatible pregnancies and to identify those who may require treatment.